2022
DOI: 10.1172/jci151895
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting SCAP/SREBP exacerbates liver injury and carcinogenesis in murine nonalcoholic steatohepatitis

Abstract: Enhanced de novo lipogenesis mediated by sterol regulatory element–binding proteins (SREBPs) is thought to be involved in nonalcoholic steatohepatitis (NASH) pathogenesis. In this study, we assessed the impact of SREBP inhibition on NASH and liver cancer development in murine models. Unexpectedly, SREBP inhibition via deletion of the SREBP cleavage–activating protein (SCAP) in the liver exacerbated liver injury, fibrosis, and carcinogenesis despite markedly reduced hepatic steatosis. These phenotypes were amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…These results demonstrated that, while liver deletion of SCAP reduced hepatic steatosis, loss of SREBP-dependent lipogenesis sensitized the liver to NASH, which resulted in increased inflammation and HCC carcinogenesis ( Figure 1 ). There was also a positive association in expression of SCAP and SREBPs in patients with NAFLD, providing some correlative evidence that the proposed pathway also has relevancy in human NASH ( 8 ).…”
Section: The Effects Of Lipid Reductionmentioning
confidence: 85%
See 4 more Smart Citations
“…These results demonstrated that, while liver deletion of SCAP reduced hepatic steatosis, loss of SREBP-dependent lipogenesis sensitized the liver to NASH, which resulted in increased inflammation and HCC carcinogenesis ( Figure 1 ). There was also a positive association in expression of SCAP and SREBPs in patients with NAFLD, providing some correlative evidence that the proposed pathway also has relevancy in human NASH ( 8 ).…”
Section: The Effects Of Lipid Reductionmentioning
confidence: 85%
“…Similar gene-expression signatures were found in isolated hepatocytes from these mice, confirming that the observed ER stress is a cell-autonomous effect due to SCAP deletion. Consistent with ER stress playing a direct role downstream of SCAP deletion, hepatic overexpression of the ER chaperone GRP78 suppressed activation of the UPR marker CHOP and partially rescued liver injury ( 8 ). SREBPs also control elongation and desaturation of fatty acids ( 10 ).…”
Section: The Effects Of Lipid Reductionmentioning
confidence: 90%
See 3 more Smart Citations